The effect of polycystic ovarian syndrome on the mental health of women of reproductive age - Adebisi, Oluwatoni D.; Denwigwe-aggrey, Blessing C.; Tairu, Ashiat Bolanle; Ozoemena, Ngozichukwu; David, Joy F.; Monday, Esther Olunu (International Journal of Research in Medical Sciences, 2021)
Polycystic ovary syndrome (PCOS) is defined as a hormonal disorder that is prevalent among women of reproductive age. It affects the metabolic, endocrine, and reproductive systems of the body as well as mental health. We compared up to 20 peer-reviewed literature that displayed the relationship between PCOS and mental health. We searched the PMC/NCBI/NIH database and we used the following keywords while searching the database: "polycystic ovarian syndrome" or "PCOS" and "mental health" or "depression" or "anxiety" or "low self-esteem" were included in the search for articles. Women of reproductive age are seen to be affected by PCOS. The effect of polycystic ovarian syndrome on the mental health of women of reproductive age has serious complications. Complications include an increased rate of anxiety and depression in the individual. When there is an increase in depression and anxiety, it tends to affect the physical changes and the confidence of women with PCOS. PCOS has been proven to be incurable but its symptoms can be managed. PCOS is linked with mental health and it has serious implications on the psychological health of the individual. Management of PCOS should include an early assessment of the patients’ mental health. If required, medications for mental health improvement should be prescribed in addition to medication for treating the physical and biochemical symptoms of PCOS.